2013
DOI: 10.1021/jf401495t
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Pentacyclic Triterpenoids from Fruits and Leaves of Olive Tree (Olea europaea L.) cv. Picual and cv. Cornezuelo during Ripening

Abstract: Pentacyclic triterpenoids are plant secondary metabolites of great interest for health and disease prevention. HPLC-UV/vis was used to determine the concentration of the pentacyclic triterpenoids present in fruits and leaves of Picual and Cornezuelo olive tree cultivars. Maslinic acid (MA) and oleanolic acid (OA) are the only two compounds present in fruits, MA being the more abundant. In leaves, in addition to MA and OA, uvaol (UO), and erythrodiol (EO) are found, with OA being the most abundant. In this work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 30 publications
(44 reference statements)
5
43
1
Order By: Relevance
“…It is well known that oleuropein (1), erythrodiol (4), uvaol (5), are the characteristic components of the olive leaf and fruits [35,39,42,43]. Ursolic acid is another characteristic component of the olive leaves besides oleanolic acid (2) and maslinic acid (3) [38,[39][40][41][42][43], whereas ursolic acid was not found in the present study. On the other hand, compounds 4 and 5 (erythrodiol and uvaol) were isolated as an only one spot on TLC due to their similar polarity ( Figure 1).…”
Section: Chemical Composition Of O Europea Leavescontrasting
confidence: 44%
See 1 more Smart Citation
“…It is well known that oleuropein (1), erythrodiol (4), uvaol (5), are the characteristic components of the olive leaf and fruits [35,39,42,43]. Ursolic acid is another characteristic component of the olive leaves besides oleanolic acid (2) and maslinic acid (3) [38,[39][40][41][42][43], whereas ursolic acid was not found in the present study. On the other hand, compounds 4 and 5 (erythrodiol and uvaol) were isolated as an only one spot on TLC due to their similar polarity ( Figure 1).…”
Section: Chemical Composition Of O Europea Leavescontrasting
confidence: 44%
“…The fractionation of the ethanol and ethyl acetate extracts of O. europea leaves by column and thin layer chromatography methods was afforded to isolation of known metabolites, one secoiridoid (1) (1) [18][19]21,24], oleanolic acid (2) [35][36][37], maslinic acid (3) [38][39][40], erythrodiol (4) and uvaol (5) [36,41] (Figure 1). It is well known that oleuropein (1), erythrodiol (4), uvaol (5), are the characteristic components of the olive leaf and fruits [35,39,42,43].…”
Section: Chemical Composition Of O Europea Leavesmentioning
confidence: 99%
“…However, after the fruit matured and reached its final size between 21 and 30 WAF, triterpenic acids, essentially maslinic acid, replaced the triterpenic diols [58]. As well, when the concentration of the pentacyclic triterpenoids present in the Picual and Cornezuelo olive fruits were measured by HPLC-UV/vis, MA and OA appeared to be the only two pentacyclic triterpenoid compounds present, with MA being more abundant in content [59]. Maslinic acid (2α,3β-dihydroxy-12-oleanen-28-oic acid, MA) is a found pentacyclic triterpene from Olea europaea L., that is particularly present in high concentrations in the olive pomace [60][61][62].…”
Section: Olive Triterpenesmentioning
confidence: 87%
“…As well, OA was found to be a novel helpful tool even when reactive or inflammatory cells have already begun to infiltrate the myocardium by suppressing myocarditis and conferring protective effects on cardiac cells and inflammatory cardiomyopathies [57]. Another study by Doronzo et al (2013) concluded that OA increases vascular endothelial growth factor (VEGF) synthesis and secretion in rat vascular smooth muscle cells (VSMC) [58][59][60][61][62][63][64][65][66][67][68][69][70][71]. VEGF action on VSMC is essential for collateral vessel formation, and poor collateral vessel formation has been proposed to lead to the pathogenesis of obesity vascular complications [71].…”
Section: Grape Skin Triterpenesmentioning
confidence: 99%
“…Thereafter, the ursanyl cation yields to ␣-amyrin from which arise uvaol and ursolic acid [2]. Triterpenic alcohols (erythrodiol and uvaol) and acids (oleanolic, ursolic and maslinic acids) have been found in Olea europaea L. leaves [3,4], whereas in the ripe fruit only oleanolic and maslinic acids have been detected [3][4][5][6]. Recently, maslinic and oleanolic acids along with traces of ursolic acid have been reported in virgin olive oil from different cultivars [7].…”
Section: Introductionmentioning
confidence: 99%